Use of pesticides in domestic animals and their importance in public health - Zanabria Ochoa, Enriquez (Revista Universidad de Guayaquil, 1991)
It is general knowledge that man incessantly searches for products of any origin to combat pests that, with their permanent competitors, keep the productivity of crops and animals always threatened and man is forced to use all available means to protect your food sources, health and economy